Complex strength-constrained topology structural optimization problem statement for rolling stock and special equipment of railway - Tovt, B. M. (Science and Transport Progress, 2013)
Purpose. The main paper purpose is the development of the topology structural optimization scientific basis regarding to the complicated optimization problems of rolling stock and special railway equipment structures. Methodology. Mathematical programming and mathematical modeling are the creating tools for the topology structural optimization problem statement for the rolling stock and special railway equipment. Findings. The fundamental review and analysis of the topology structural optimization modern state is executed. The classical variation problem statement and FE-statement of the topology optimization problem are in the paper. The stress-constrained structure mass minimization problem statement is considered. The stress-constrained topology optimization problems have some difficulties, which are considered in the paper in detail. The strength condition by the fatigue strength safety factor criterion is transformed to the strength condition by the allowable stresses criterion. Originality. Scientific novelty is the development of the optimal design theory adapted to solving the rolling stock and special railway equipment structures problems. Practical value. Practical importance of the research is the adaptation of the existing topology structural optimization problem statements to the railway engineering industry problems.